Psychological impacts on adults during the COVID-19 pandemic: an integrative review (Research, Society and Development, 2021)
COVID-19, a disease caused by the new coronavirus, was discovered in November 2019 in the city of Wuhan, China. With the expansion of the disease and its pandemic character, the damage to health has increased, as well as the impacts on the mental health of the global population, generating the need for psychological support. The aim of the study was to analyze the psychological impacts on adults caused by the COVID-19 pandemic. An integrative literature review was carried out, based on primary articles from the Scientific Electronic Library Online (SCIELO) and Latin American and Caribbean Health Sciences (LILACS) databases. Eighteen articles related to the topic were found. The data presented in this study reinforce the theory that the COVID-19 pandemic caused significant changes in the lives of adults, especially with regard to the diagnosed psychological impacts, changes in lifestyle and the impact on people's feelings, as well as self-perception of mental health during the pandemic. The study concluded that the most common psychological impacts during the pandemic were anxiety, depression and stress. The most evident feelings were fear, sadness and concern about illness due to COVID-19, causing sleep disorders, decreased physical activity and increased consumption of processed foods.